Antimicrobial photodynamic inactivation of Pseudomonas aeruginosa persister cells and biofilms - Mona Mahmoud; Peter Richter; Philipp Arnold; Michael Lebert; Andreas Burkovski (Photodiagnosis and Photodynamic Therapy)
Pseudomonas aeruginosa is a hard-to-treat human pathogen for which new antimicrobial agents are urgently needed. P. aeruginosa is known for forming biofilms, a complex aggregate of bacteria embedded in a self-generated protective matrix that enhance its resistance to antibiotics and the immune system. Within the biofilm, persister cells, sub-populations of slow-growing or growth-arrested cells, are associated with recalcitrance of infections and antibiotic treatment failure. Here, we investigate the influence of the anionic photosensitiser chlorophyllin (CHL)11 Abbreviations: CHL: Chlorophyllin; BP: Butylparaben; SHX: Serine hydroxamate; TEM: Transmission electron microscope; AMR: Antimicrobial resistance; aPDI: Antimicrobial photodynamic inactivation; LED: Light-emitting diodes exposed to red light alone and in combination with an activator of the mechanosensitive channels butylparaben (BP) on P. aeruginosa growing cells, persister cells, and biofilms. Antimicrobial susceptibility tests were performed using the broth microdilution checkerboard method. Serine hydroxamate (SHX) was used for the induction of persister cells. Under illumination, a combination of CHL (250 µg/ml) and BP (97.12 µg/ml) reduced the number of growing cells and persister cells by 2.2±0.46 log10 and 1.7±0.15 log10, respectively after 30 min of exposure at 79 J/cm2. A higher concentration of BP (194.23 µg/ml) or longer exposure time (60 min at 158 J/cm2) effectively eliminated approximately ≥99.99 % of growing and persister cells. Visual evidence from confocal and TEM images illustrates the influence of CHL and red light, which intensifies when combined with BP. Nevertheless, the addition of BP did not enhance the efficacy of CHL against biofilms; CHL (500 µg/ml) reduced biofilm viability by 2.6 log10 at 791 J/cm2. No toxicity has been observed in darkness. This study highlights the potential antimicrobial effect of CHL against P. aeruginosa.